The Portrait of Villain in Horror Movie Await Further Instructions - Sarman Samarudin; Muarifuddin Muarifuddin (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research aims to describe the portrait of the villain in the horror movie Await Further Instructions with a formulaic approach by J. G. Cawelti to provide an overview of movie development, especially the villain elements in horror movies. The descriptive-qualitative method was used in this research. The data for this research were collected by watching, pausing, identifying, classifying, and then analyzed by presenting, describing, and interpreting the data as well as concluding the analysis result. This research found four villain elements that are the same as horror villains in general (convention) and two different elements of villain (invention) that depict new sources of fear, such as motive antagonist (constructed by the media) and iconic symbol (mass media). The researcher concluded that in the horror movie Await Further Instructions, there is development in the elements of the villain that depict or represent people today being more afraid of mass media power than supernatural or unexplainable powers, such as ghosts, aliens, monsters, serial killers, and others.